Electroacupuncture Relieves Suppression of Autophagy in Interstitial Cells of Cajal of Diabetic Gastroparesis Rats - Xing Wei; Yaping Lin; Dongfeng Zhao; Xiaojuan Xiao; Qiao Chen; Siyi Chen; Yan Peng (Canadian Journal of Gastroenterology and Hepatology)
Background. The incidence of diabetic gastroparesis (DGP) is mainly blamed to abnormity of interstitial cells of Cajal (ICCs). Autophagy could degrade damaged proteins and organelles to keep intracellular homeostasis, and it could directly influence structure and number of cells. In this study, we aimed to figure out the relationship between DGP and autophagy of ICCs. Methods. Sixty Sprague-Dawley (SD) rats were randomly divided into normal control group (NC, 10) and modeling group (50). Rats in the modeling group were injected 2% streptozotocin (STZ) and fed with high-glucose and high-fat diet for 8 weeks in order to establish DGP rat model. After modeling, 30 successfully modeled rats were randomly selected and separated into diabetic gastroparesis group (DGP, 10), GDP rats with electroacupuncture group (EA, 10), and GDP rats with metoclopramide group (MP, 10). When the intervention was completed, blood glucose was measured by ONE TOUCH glucometer and gastrointestinal propulsive rate was detected through measuring optical density. Autophagosomes were observed under transmission electron microscope (TEM). The expression of LC3 protein and P62 protein was measured by Western blot. When ICCs were transfected with GFP-RFP-LC3 plasmid, autophagy flux was observed by laser scanning confocal microscope. Results. (1) After intervention, compared with blood glucose of rats in the NC group, all of the DGP, EA, and MP groups were remarkably increased (P<0.01); compared with the DGP group, the blood glucose of the EA and MP groups was decreased greatly (P<0.01). (2) Compared with gastrointestinal propulsive rate of rats in the NC group, no matter gastric emptying rate or intestinal propulsive rate, the EA and MP groups were significantly reduced (P<0.01); compared with the NC group, gastric emptying rate and intestinal propulsive rate in the EA group were obviously decreased (P<0.05, P<0.01); compared with the DGP group, the EA and MP groups were increased significantly (P<0.01). (3) Compared with the NC group, intensity of RFP and GFP in the DGP group was obviously increased (P<0.05, P<0.01), in other words, the DGP group accompanying suppression of autophagy; compared with the DGP group, intensity of RFP and GFP in the EA group was decreased significantly (P<0.05, P<0.01). (4) There was no autophagosome in the NC group, and an autophagosome existed in the DGP group. Both EA and MP groups found autophagy. (5) When coming to LC3 II/LC3 I, compared with the NC group, the ratio was enhanced in the DGP and EA groups (P<0.01, P<0.05); compared with the DGP group, LC3 II/LC3 I was dramatically decreased in the MP and EA groups (P<0.01). (6) As the substrate of degradation, the expression of P62 in the other three groups was significantly increased (P<0.01) compared with the NC group; compared with the DGP group, the amount of P62 in the EA and MP groups was reduced greatly (P<0.01). Conclusion. The impaired autophagy flux in ICCs is the pathological basis of diabetic gastroparesis, blaming to fusion dysfunction of autophagosome and lysosome and electroacupuncture (EA) could ease the suppression of autophagy to improve gastric motility.